The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/smll.202207348
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Magnetic Mesoporous Carbon Derived Nano‐Adsorbent for Synchronized Toxic Metal Removal and Bacterial Disinfection from Water Matrices

Abstract: Contamination of water resources by toxic metals and opportunistic pathogens remains a serious challenge. The development of nano‐adsorbents with desired features to tackle this problem is a continuously evolving field. Here, magnetic mesoporous carbon nanospheres grafted by antimicrobial polyhexamethylene biguanidine (PHMB) are reported. Detailed mechanistic investigations reveal that the electrostatic stabilizer modified magnetic nanocore interfaced mesoporous shell can be programmatically regulated to tune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…It was observed that the uptake of PSMMs by AFZ increased from pH values of 1.0 to 7.0 until a sharp fall was observed at pH > 7.0. ,, The plausible reason for the protonation of the surface of AFZ at pH ≤ 7.3 and the possession of a positive zeta potential is the modification of coffee waste (a starting material for AFZ synthesis) with concentrated phosphoric acid. Moreover, at pH > PZC, the solution possessed greater negative charges that improved the uptake of PSMMs by AFZ. A positive zeta potential shows an increase in the hydrophobic interaction between the target contaminant and adsorbent. In this case, the positive zeta potential increased the hydrophobic interaction between PSMMs and AFZ through π–π interactions, van der Waal interactions, and hydrogen bonding …”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the uptake of PSMMs by AFZ increased from pH values of 1.0 to 7.0 until a sharp fall was observed at pH > 7.0. ,, The plausible reason for the protonation of the surface of AFZ at pH ≤ 7.3 and the possession of a positive zeta potential is the modification of coffee waste (a starting material for AFZ synthesis) with concentrated phosphoric acid. Moreover, at pH > PZC, the solution possessed greater negative charges that improved the uptake of PSMMs by AFZ. A positive zeta potential shows an increase in the hydrophobic interaction between the target contaminant and adsorbent. In this case, the positive zeta potential increased the hydrophobic interaction between PSMMs and AFZ through π–π interactions, van der Waal interactions, and hydrogen bonding …”
Section: Resultsmentioning
confidence: 99%
“…However, the mixed solution of Mn and Fe inhibits the removal rate of Sb­(III) ions, and the maximum uptake can reach only up to 0.61 mg·g –1 . This could be due to the competition among Sb­(III) ions and Mn­(II) for adsorption sites, specific ionic potential, and smaller hydrated ionic radius . Therefore, the manganese ion is the competitive ion for MSNs to remove Sb­(III) from aqueous matrices.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, many technologies have been developed for Sb­(III) removal from wastewater, such as coagulation bioremediation, membrane filtration, electrochemical deposition, and adsorption . Mostly, these approaches require high-end maintenance and energy; however, adsorption is most effective due to its low cost, simplicity, recyclability, and high efficiency. Many adsorbents have been developed so far for heavy metal ion adsorption from water, and these can be categorized as inorganic, ,, organic, and biomass-derived. Activated carbon is a highly effective Sb­(III) adsorbent due to its large surface area and porosity. However, it has been reported that the adsorption capacity of activated carbon decreases with increasing pH, which may limit its effectiveness in certain applications .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To synchronously obtain high optical transparency and antibacterial property, the antibacterial agent should have excellent bactericidal action and comparable refractive index to PS. Polyhexamethylene guanidine (PHMG) is lethal to most bacteria, and the effect takes quickly, [13][14][15][16] which shows a promising potential in water purification, 17 air filtration, 18 and equipment. [19][20][21] The organic PHMG can be rapidly adsorbed to the negatively charged bacterial cell surface.…”
Section: Introductionmentioning
confidence: 99%